Public Procurement Electronic Platforms Assessment: Legal Requirements - Cunha, Sandra (2019)
Electronic public procurement (EPP) has been considered an important tool for promoting competition, simplifying procedures, and ensuring transparency in decision-making processes. In Portugal, EPP replaced paper-based pre-contractual procedures for communication and processing. Addressing this general issue, the authors designed and proposed TrivPlat, a free access tool for monitoring, managing, and evaluating electronic platforms of public procurement. This paper presents the TrivPlat project, reporting its development so far: the identification and characterization of legal requirements that electronic platforms for public procurement are required to follow in Portugal. Legal requirements may be grouped into four types: general operating rules, functional requirements, technical requirements, and safety requirements. The first phase of the TrivPlat project's diagnosis is expected to result in the development of an aggregate evaluation framework for public procurement platforms in order to reach the fundamental principles: equality of treatment, confidenciality, traceability, effectiveness, compatibility, interoperability, security and general availability.